CHANGES IN MINERAL METABOLISM OF CATS WITH DENTAL RESORPTION PATHOLOGY - Zvenihorodska, T. V.; Kyrychko, B. P. (Scientific Progress & Innovations, 2020)
The etiology of cat pathological resorption of teeth has not been fully studied. In papers of many scien-tists it is specified that pathological resorption is directly connected with poor calcium containing diet (meat and by-products), which is evidenced by decreasing radio density of scleromeninx plate, alveolar bone, and horizontal alveolar losing bone weight. Consequently, meat diet with low calcium content or increased phosphorus content causes temporary hypocalcemia, and it, in its turn, stimulates the synthesis of parathy-roid hormone. The hormone stimulates osteoblasts and leads to bone tissue resorption. A group of cats with pathological tooth resorption (experimental) and a group of clinically healthy animals (control) were taken for the study; each group had six cats. The control group included healthy animals with intact periodontal membrane; and experimental group included cats aged from four to nine years old with pathological tooth resorption. The disease was diagnosed based on anamnesis, visual examination of the oral cavity and X-ray images, which were made on “Armand” 9l5 device using intra-oral Kodak 2 × 3 cm film, 50 kV rigidity and exposition of 4 mA/s. Animals’ blood samples, oral liquid and urine were selected by commonly known methods for testing. It has been proven that at pathological tooth resorption of domestic cats, increased cal-cium content in blood serum and oral fluid, deoxypyridinoline in urine are registered, as well as reduced vitamins A (p<0.05), E (p<0.001), and D3 (p<0.05) content in blood serum as compared with the group of clinically healthy cats. In the urine of cats with pathological resorption, an increased DPID content (P<0.05) has been found. Measurements of specific bone matrix degradation products characterize the rate of bone metabolism. Under pathological conditions, these processes are separated and, if resorption exceeds synthesis, bone weight loss is observed.